DFROG‐MAC: A Dynamic Fragmentation‐Based MAC for Prioritised Emergency Data Management in Vehicular Networks - Anwar Ahmed Khan (23718879) (2025)
The rapid advancements in vehicular ad hoc networks (VANETs) call for development of effective networking schemes. Managing heterogenous traffic in VANETs becomes a critical challenge, especially when dealing with critical scenarios. In this paper, we present a novel dynamic fragmentation‐based MAC protocol, DFROG‐MAC for Internet of Things (IoT) applications in VANET environment. This protocol is focused on facilitating prioritised heterogenous traffic in sensor networks and hence, can offer a distinguished quality of service for various application areas such as vehicular, industrial or body sensor networks. DFROG‐MAC deploys fragmentation scheme for low priority data, so the high priority data may interrupt and access channel without needing to wait for the complete transmission of lower priority data. The fragment size for the lower priority data is dynamically adjusted at the runtime based on the frequency of urgent traffic arrival. This dynamic approach helps to ensure that the channel does not remain idle, and lower priority traffic could be served quickly, in the absence of urgent traffic. Two types of traffic priorities, normal and urgent have been used for performance evaluation of FROG‐MAC and DFROG‐MAC, over Contiki platform, with the scope of this study focused on vehicle‐to‐infrastructure (V2I) single‐hop communication. The delay and throughput both have been found to improve for DFROG‐MAC due to the possibility of dynamic fragment size selection. Other Information Published in: IET Wireless Sensor Systems License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/wss2.70017